Diagnosis dan Tata Laksana Cedera Ligamen Cruciatum Anterior - Adhitya Prabawa, I Wayan Ryan (Cermin Dunia Kedokteran, 2024)
In the world of sports, the anterior cruciate ligament (ACL) plays a very important role in maintaining the stability and function of the knee joint. ACL injuries are most common in 20 to 40 years old and can be caused by unbalanced physical conditions, which can lead to problems such as loss of strength, stability, and mobility. If not treated properly, ACL injuries can lead to movement disorders.